Prevention, mitigation and adaptation to climate change from perspectives of urban population in an emerging economy (2018)
This paper discusses the current knowledge and opinions of urban population in a city of a country that it is recognized with greater vulnerability to climate change, as it is Bogotá the main city of Colombia. It is important to analyse the opinion of the urban population on climate change, taking into account that in the next years cities will be vulnerable and affected by this phenomenon. This research uses a survey that determine the knowledge, causes and effects of climate change, as well as measurements and information that are required to address climate change issues more fully. The main results suggest that the Bogotá's respondents have heard about climate change and all consider that this phenomenon is a reality. The main effects of climate change according to respondents are droughts and floods, with consequences for health and water, energy and food availability. Moreover, the respondents consider the design and application of adequate measurements that allow adaptation and mitigation to climate change important. The findings of this study are significant for awareness at all levels of urban society of the activities and programs that allow for sustainable development in consideration of climate change. © 2018 Elsevier Ltd